Lutein Has a Protective Effect on Hepatotoxicity Induced by Arsenic via Nrf2 Signaling. (26th February 2015) - Li, Shugang; Ding, Yusong; Niu, Qiang; Xu, Shangzhi; Pang, Lijuan; Ma, Rulin; Jing, Mingxia; Feng, Gangling; Tang, Jing Xia; Zhang, Qian; Ma, Xiaomei; Yan, Yizhong; et al.
Abstract : Arsenic produces liver disease through the oxidative stress. While lutein can alleviate cytotoxic and oxidative injury, nuclear factor erythroid 2-related factor 2 (Nrf2) pathway plays a critical role in defending oxidative species. However, the mechanisms by which lutein protects the liver against the effect of arsenic are not known. Therefore, this study aims to investigate the mechanisms involved in the action of lutein using mice model in which hepatotoxicity was induced by arsenic. We found that mice treatment with lutein could reverse changes in morphological and liver indexes and result in a significant improvement in hepatic function comparing with arsenic trioxide group. Lutein treatment improved the activities of antioxidant enzymes and attenuated increasing of ROS and MDA induced by arsenic trioxide. Lutein could increase the mRNA and protein expression of Nrf2 signaling related genes ( Nrf2, Nqo1, Ho-1, and Gst ). These findings provide additional evidence that lutein may be useful for reducing reproductive injury associated with oxidative stress by the activation of Nrf2 signaling. Our findings suggest a possible mechanism of antioxidant lutein in preventing the hepatotoxicity, which implicate that a dietary lutein may be a potential treatment for liver diseases, especially for arsenicosis therapy.